Exploring the impact of perceived risk and trust on tourist acceptance intentions in the post-COVID-19 era: A case study of Hainan residents - Zhou, Hongxia; Ibrahim, Johan Afendi Bin; Mohamed, Ahmad Edwin Bin (Frontiers in Psychology, 2022)
Hainan, is the only free trade port which also exudes quintessence of the culture of China. Tourism is one of Hainan’s most lucrative industries. On one hand, the regional economy is flourishing and on the other hand, the economy is facing unprecedented impacts from the COVID-19 pandemic. In response to the affected global market environment, this study investigates Hainan residents’ acceptance intentions, or tolerance, of tourists. Here, based on the theory of reasoned action, which includes: "subjective norm" combined with "trust", "perceived risk", and "perceived value”. Using "resident attitude" as a mediator, research theoretical frameworks were established. A total of 447 surveys from online and paper-copy questionnaires were distributed to Hainan residents, from July 15, 2021 to November 10, 2021. With data from the questionnaires were analyzed in three stages: descriptive statistical analysis, measurement model verification, and structural equation modeling analysis. Findings show a positive effect of trust on residents’ attitudes in Hainan; perceived value and subjective norm showed a positive effect on resident acceptance intentions for tourism; the perceived risk of residents showed a more negative effect on attitudes toward tourists, but the influence is small. Finally, through the results of the study, theoretical and practical implications in a post-pandemic era are discussed.